2003
DOI: 10.1103/physreve.67.011904
|View full text |Cite
|
Sign up to set email alerts
|

Structure of self-assembled liposome-DNA-metal complexes

Abstract: We have studied the structural and morphological properties of the triple complex dioleoyl phosphatidylcholine (DOPC)-DNA-Mn2+ by means of synchrotron x-ray diffraction and freeze-fracture transmission electron microscopy. This complex is formed in a self-assembled manner when water solutions of neutral lipid, DNA, and metal ions are mixed, which represents a striking example of supramolecular chemistry. The DNA condensation in the complex is promoted by the metal cations that bind the polar heads of the lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
59
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 57 publications
10
59
0
Order By: Relevance
“…3) (see also Uhríková et al, 2002;2005a). Our short analysis indicates no marked (Francescangeli et al, 2003) and also in the liquid -crystalline phase of DPPC : DNA=8 : 1 (mol/base) aggregates at 1 -100 mM Ca 2+ (McManus et al, 2003b), where mechanism of interaction and models of coexistence of both phases were proposed. Our previous work (Uhríková et al, 2005a) documents that such structure forms also DOPC + DNA in a wide range of cations concentrations (0 -76.5 mM of Ca 2+ or Mg 2+ ).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…3) (see also Uhríková et al, 2002;2005a). Our short analysis indicates no marked (Francescangeli et al, 2003) and also in the liquid -crystalline phase of DPPC : DNA=8 : 1 (mol/base) aggregates at 1 -100 mM Ca 2+ (McManus et al, 2003b), where mechanism of interaction and models of coexistence of both phases were proposed. Our previous work (Uhríková et al, 2005a) documents that such structure forms also DOPC + DNA in a wide range of cations concentrations (0 -76.5 mM of Ca 2+ or Mg 2+ ).…”
Section: Resultsmentioning
confidence: 54%
“…For DPPC:DNA=8:1 mol/base aggregates formed in presence of 1-100 mM CaCl 2 , the coexistence of two lamellar phases was reported (McManus et al, 2003a, b), one with DNA strands intercalated in the water layer between lipid bilayers with a repeat distance d~8.0-7.4 nm and another one with a repeat distance d~6.6-5.6 nm, which was interpreted as a phase formed by lipid bilayers only. Francescangeli et al (2003) observed also the coexistence of two lamellar phases in aggregates of DOPC+DNA+Mn 2+ . The coexistence of two lamellar phases in one aggregate formed by DOPC+DNA in the concentration range 0-76.5 mM of metal cations (Ca 2+ or Mg 2+ ), effect of temperature, DOPC:DNA molar ratio, and length of DNA fragments were studied in our recently published work (Uhríková et al, 2005a).…”
Section: Introductionmentioning
confidence: 72%
“…Structural studies of both the cationic and zwitterionic DNA lipoplexes have been reported over the past number of years. [4][5][6][13][14][15][16][17][18][19][20][21] However, here we show for the first time that, in addition to the enhanced divalent cation binding, 17 this complex is capable of arranging DNA into higher orders of local organization.The complex is prepared by mixing DNA (calf thymus, purified by a method described before 18 ), unilamellar liposomes of DPPC, prepared by bath sonication at 50°C, and calcium from concentrated stocks in the wide part of a 1 mm X-ray capillary. The complex was allowed to form for 1 h before being centrifuged to the end of the capillary and equilibrated by a cycle of heating and cooling, above and below the melt transition temperature of the lipid over a number of days.…”
mentioning
confidence: 99%
“…Structural studies of both the cationic and zwitterionic DNA lipoplexes have been reported over the past number of years. [4][5][6][13][14][15][16][17][18][19][20][21] However, here we show for the first time that, in addition to the enhanced divalent cation binding, 17 this complex is capable of arranging DNA into higher orders of local organization.…”
mentioning
confidence: 99%
See 1 more Smart Citation